Photocurrent response and semiconductor characteristics of Ce-Ce(2)O(3)-CeO(2)-modified TiO(2) nanotube arrays - Tan, Yu (Springer, 2014)
We reported Ce and its oxide-modified TiO(2) nanotube arrays (TNTs) and their semiconductor properties. The TNTs were prepared by anodic oxidation on pure Ti and investigated by electrochemical photocurrent response analysis. Then, the TNT electrodes were deposited of Ce by cathodic reduction of Ce(NO(3))(3) 6H(2)O. After deposition, the TNT electrodes were fabricated by anodic oxidation at E = 1.0 V((SCE)) for various electricity as Ce-Ce(2)O(3)-CeO(2) modification. The Ce-deposited TNTs (band gap energy E(g) = 2.92 eV) exhibited enhanced photocurrent responses under visible light region and indicated more negative flat band potential (E(fb)) compared with the TNTs without deposition. After anodic oxidation, the mixed Ce and its oxide (Ce(2)O(3)-CeO(2))-modified TNT photoelectrodes exhibited higher photocurrent responses under both visible and UV light regions than the TNTs without deposition. The photocurrent responses and E(fb) were found to be strongly dependent on the contents of Ce(2)O(3) and CeO(2) deposited on TNTs. A new characteristic of E(g) = 2.1 ± 0.1 eV was investigated in the Ce(2)O(3)- and CeO(2)-modified photoelectrodes. X-ray diffraction (XRD), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS) were also employed to characterize various modified TNTs photoelectrodes.